Arkitektura a documentary on Philippine ethnic architecture - Perez, Rodrigo D.; Hila, Ma. Corazon A. (Tuklas sining series, 1992)
Describes the historical development of ethnic architecture, from cave dwellings to lean-to and tree houses, and the typical ethnic houses we find today. Also compares and contrasts the various forms of ethnic houses found in the different provinces of the Philippines.